Ultrasound Image Segmentation based on Information Diffusion Model - Subhamathi, Ajitha R (International Journal of Computer Sciences and Engineering, 2025)
Medical image segmentation is one of the fundamental and classic problem in computer aided diagnosis. Among different segmentation techniques, graph theoretical approaches attracted much research attention since it have many good features in practical applications. This work is an attempt in this direction. In this article a graph based approach for segmentation on ultrasound image is proposed. It makes use of information diffusion model in social networks. Proposed method is tested on a set of real ultrasound images and the result is compared with other graph based approaches. Computational complexity of this approach is comparatively less.